Digital activism and collective resistance to police brutality: Systematic review of the quieter and less visible narratives of #EndSARS protest - Emma Etim; Jacob O. Fatile; Joseph Eyo Duke; Busayo Qazeem Ibikunle; Emmanuel J.C. Duru (Social Sciences and Humanities Open, 2025)
While Twitter (X) thrived as a site of expression during the #EndSARS protest, how many stories were left untold and buried in the quiet corners of rural communities with limited internet access? This systematic literature review (SLR) analysed 19-peer-reviewed articles published between 2020 and 2024 to synthesise available evidence on overlooked narratives and the significant but underexplored roles of platforms other than X, such as Facebook, Instagram, and WhatsApp, in digital activism and mobilisation. We found a general agreement that digital media played a crucial role in exposing police brutality and amplifying the demands for accountability. However, this dominant framing, centred on urban and online activism, risks obscuring the quieter, less visible narratives that unfolded in rural communities and places where internet access is limited or entirely absent. In rural areas, protests took different forms, including oral storytelling, community gatherings, handwritten placards, and symbolic acts rooted in local traditions, all of which targeted the call for action. These offline framing strategies are also significant. This is because protest is not only what trends but also what endures in memory, ritual, and local resistance.